Local Activities of Hydroxide and Water Determine the Operation of Silver‐Based Oxygen Depolarized Cathodes. Issue 38 (28th August 2018) - Botz, Alexander; Clausmeyer, Jan; Öhl, Denis; Tarnev, Tsvetan; Franzen, David; Turek, Thomas; Schuhmann, Wolfgang
Abstract: Local ion activity changes in close proximity to the surface of an oxygen depolarized cathode (ODC) were measured by scanning electrochemical microscopy (SECM). While the operating ODC produces OH − ions and consumes O2 and H2 O through the electrocatalytic oxygen reduction reaction (ORR), local changes in the activity of OH − ions and H2 O are detected by means of a positioned Pt microelectrode serving as an SECM tip. Sensing at the Pt tip is based on the pH‐dependent reduction of PtO and obviates the need for prior electrode modification steps. It can be used to evaluate the coordination numbers of OH − ions and H2 O, and the method was exploited as a novel approach of catalyst activity assessment. We show that the electrochemical reaction on highly active catalysts can have a drastic influence on the reaction environment. Abstract : Local ion activity changes in close proximity to the surface of a working oxygen depolarized cathode (ODC) were determined using the shift of the pH‐dependent PtO reduction potential at a closely positioned Pt microelectrode. The operating ODC produces OH − ions and consumes oxygen and water during the oxygen reduction reaction, and hence has a drastic influence on the local reaction environment.